Development of the Renminbi Market in Hong Kong SAR : Assessing Onshore-Offshore Market Integration - Craig, R. (IMF Working Papers; Working Paper ;, 2014)
Offshore use of the renminbi expanded rapidly in Hong Kong SAR as China sought to develop an international role for its currency while maintaining capital controls. This prompts two questions addressed in this paper: How far advanced is renminbi internationalization? And, what role does Chinese capital account liberalization play? The first is addressed by testing the extent of integration of offshore and onshore markets for the renminbi using a Threshold Autoregression (TAR) model and finds that there are substantial unexploited arbitrage opportunities. A VAR model is used to indentify factors contributing to this limited market integration and finds that capital controls and shifts in global market sentiment explain much of the divergence in onshore and offshore renminbi exchange rates. To address the second question, the paper shows how capital account measures have been used to promote offshore use of the renminbi more actively in the wake of the global financial crisis, but that this was done asymmetrically with controls on inflows eased to a greater extent than on outflows. It concludes that a more balanced liberalization process will sustain progress in renminbi internationalization.